Yhwh, Moses, and Pharaoh: Masculine competition as rhetoric in the exodus narrative - Purcell, Richard (Journal for the study of the Old Testament, 2020)
This article contends that ancient Near Eastern gender ideals concerning masculinity are brought to bear by the Exodus narrative to shape an effective rhetoric, a rhetoric which compares and contrasts the primary male characters of the narrative: Yhwh, Moses, and Pharaoh. The text portrays these male characters as variously fulfilling or failing to meet ancient Near East masculine ideals in order to array Yhwh, Moses, and Pharaoh in relation to one another as effective males. In doing so, the text casts Yhwh as a male character who meets the ideal, Pharaoh as a male character who falls short of the ideal, and Moses as a male character who wavers in between the two. By drawing upon ancient gender ideals to shape its rhetoric, the text reinforces these gender ideals, rather than deconstructing them.